Outcomes of morbidly obese patients undergoing total hip arthroplasty with the anterior-based muscle-sparing approach. (2nd May 2023) - Shevenell, Bailey E.; Mackenzie, Johanna; Fisher, Lillian; McGrory, Brian; Babikian, George; Rana, Adam J.
Abstract : Aims: Obesity is associated with an increased risk of hip osteoarthritis, resulting in an increased number of total hip arthroplasties (THAs) performed annually. This study examines the peri- and postoperative outcomes of morbidly obese (MO) patients (BMI ≥ 40 kg/m 2 ) compared to healthy weight (HW) patients (BMI 18.5 to < 25 kg/m 2 ) who underwent a THA using the anterior-based muscle-sparing (ABMS) approach. Methods: This retrospective cohort study observes peri- and postoperative outcomes of MO and HW patients who underwent a primary, unilateral THA with the ABMS approach. Data from surgeries performed by three surgeons at a single institution was collected from January 2013 to August 2020 and analyzed using Microsoft Excel and Stata 17.0. Results: This study compares 341 MO to 1, 140 HW patients. Anaesthesia, surgery duration, and length of hospital stay was significantly lower in HW patients compared to MO. There was no difference in incidence of pulmonary embolism, periprosthetic fracture, or dislocation between the two groups. The rate of infection in MO patients (1.47%) was significantly higher than HW patients (0.14%). Preoperative patient-reported outcome measures (PROMs) show a significantly higher pain level in MO patients and a significantly lower score in functional abilities. Overall, six-week and one-year postoperative data show higher levels of pain, lower levels of functional improvement, and lower satisfaction scores in the MO group. Conclusion: The comorbidities of obesity are well studied; however, the implications of THA using the ABMS approach have not been studied. Our peri- and postoperative results demonstrate significant improvements in PROMs in MO patients undergoing THA. However, the incidence of deep infection was significantly higher in this group compared with HW patients. Cite this article: Bone Jt Open  2023;4(5):299–305.